Cognitive Risk Factors Predicting Social Anxiety among Indonesian Adolescents - Muhammad Salis Yuniardi (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2019)
Social anxiety is the third largest mental problem over the world, but no study has investigated cognitive risk factors predicting social anxiety among Indonesian adolescents. This study aimed to investigate the role of fear of negative evaluation, anxiety sensitivity and intolerance of uncertainty in predicting their social anxiety. There were 162 senior high school students completed the paper and pencil questionnaire. Regression analyses was utilised in order to examine the relative contributions, being followed by moderation analyses in order to investigate any possible interaction among the risk factors examined. The result reveals that the contribution of fear of negative evaluation and anxiety sensitivity were significant, but the former was dominant. In addition, there was interaction between them where decreasing the effect of each other. Interestingly, intolerance of uncertainty did not contribute significantly to the model.